«Embodiment of the ideal» as a factor in the artistic and aesthetic development of Russian literature of the 19th century - Bashkirau, Dzmitry L. (Journal of the Belarusian State University. Philology, 2025)
The issue of the literary and aesthetic system within the development of Russian literature of the 19th century (realism) is examined. Most questions related to realism revolve around the monological nature of the Eurocentric model of cultural development, which underpins the study and understanding of artistic phenomena, contradicting the essence of the unique spiritual phenomenon – East Slavic literacy. A new perspective on this problem, the essence of which reflects the concept of the «embodiment of the ideal», is proposed. The formation of the artistic and aesthetic principles of Russian literature was influenced by the movement of meanings and the flow of condensed connections that arose within the enlightening activities of Cyril and Methodius («translation»), which on East Slavic soil formed a literacy that represented the «core». The totality of the dynamic manifestations of the «core» in the cultural and historical environment created the architectonics of value-aesthetic relations – the «embodiment of the ideal».